Income Level of Working Women in Siatele Village, North Seram District - Welminci Timanoyo; M. Turukay; F.P. Adam (Cita konsultindo, 2023)
This study aims to find out how the income level of Siatele Village women and the reasons why Siatele Village women decide to work. This research is a descriptive qualitative research. Data collection method through in-depth interviews and observations. The method of census sampling of women working in the public sector was 41 respondents. The results showed that the income level of Siatele Village women sourced from employees amounted to IDR 2,080,000-2,496,000, civil servants IDR 3,300,000, Honor Teachers IDR 200,000-500,000 and Entrepreneurs IDR 500,000-1,950,000 and Farmers IDR 216,000-860,000. Working women’s income contributes to family income by 49 percent. The reason women work is dominated by factors Increasing family income by 46 percent, children’s education by 22 percent, company attendance by 20 percent and Filling leisure time by 12 percent.